2018
DOI: 10.1007/s10157-018-1632-9
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and effectiveness of long-term use of darbepoetin alfa in non-dialysis patients with chronic kidney disease: a post-marketing surveillance study in Japan

Abstract: This PMS study showed the safety and effectiveness of long-term use of darbepoetin in a large number of patients. Patients with Hb ≥ 11 g/dL presented fewer composite renal endpoints than those with Hb < 11 g/dL, without an increase in the incidence of cardiovascular-related AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The relationship between ESA therapy for anemia of kidney disease and kidney outcome in predialysis patients with CKD has been investigated in various small-and largescale RCTs and observational studies over the past two decades (4)(5)(6)(7)(8)21,22). Particularly, in the Cardiovascular Risk Reduction by Early Anemia Treatment with Epoetin Beta study, targeting hemoglobin levels of 13-15 g/dl resulted in more frequent dialysis initiations than targeting hemoglobin levels of 10.5-11.5 g/dl (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between ESA therapy for anemia of kidney disease and kidney outcome in predialysis patients with CKD has been investigated in various small-and largescale RCTs and observational studies over the past two decades (4)(5)(6)(7)(8)21,22). Particularly, in the Cardiovascular Risk Reduction by Early Anemia Treatment with Epoetin Beta study, targeting hemoglobin levels of 13-15 g/dl resulted in more frequent dialysis initiations than targeting hemoglobin levels of 10.5-11.5 g/dl (7).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, ESA doses used in Japan seems to be lower than those used in Western countries. A nationwide cohort study conducted on more than 5000 patients with predialysis CKD in the real-world clinical setting in Japan showed that hemoglobin levels had been maintained between 10.0 and 10.6 g/dl for about 3 years using darbepoetin alfa, with the mean dose of 17.1 mg/wk (22). Furthermore, previous reports revealed that the erythropoietin-resistance index was about two times higher in Western patients with CKD than in Japanese patients with CKD (24-27).…”
Section: Discussionmentioning
confidence: 99%
“…ESA hyporesponsiveness is a strong predictor of mortality and CVD events as well as poor renal survival in patients with CKD [ 16 , 17 , 21 25 ]. Although the definition of ESA hyporesponsiveness has been suggested in previous clinical guidelines for the treatment of anemia in patients with CKD, they were defined arbitrarily and were not associated with any outcomes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This definition was based on the secondary analysis of the TREAT study, which revealed that diabetic pre-dialysis CKD patients with initial hyporesponsiveness to DA had poor cardiovascular outcome [ 17 ]. However, in the TREAT study, nearly half of study subjects had CVD and the DA dose used was quite different from those used in our clinical practice setting in Japan [ 15 , 25 ]. Therefore, extrapolating this definition into clinical practice in Japan seems difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The AEs reported in this study were lesser than the popular DREAM-J surveillance study of long-term use of darbepoetin alfa in non-dialysis patients with CKD. DREAM-J study reported 44.4% AEs [6]. This PMS study result suggests that there is no apparent risk for life-threatening or SAEs under clinical conditions where DA-α (manufactured by Hetero Biopharma) is prescribed for the management of anemia associated with CKD.…”
Section: Discussionmentioning
confidence: 73%